Multivariate assessment of automated massage chair efficacy on skin tissue perfusion and sleep metrics / Ayan Paul - Ayan, Paul (2021)
Stress and sleep-related disorders are increasingly becoming more prevalent among adult population. Manual massage therapy (MMT) may assist in improving the peripheral circulation through mechanical manipulation of soft tissues and passively act upon reducing stress stimuli and in turn, may induce relaxation and sleep. For the purpose of evaluating the efficacy of massage chair therapy (MCT), this study is divided into three parts. First, a randomized controlled, cross-over, repeated measures and single-blinded trial involving 17 participants (age 21.76 ± 1.20 years; weight 52.50 ± 9.19 kg; height 163.50 ± 17.68 cm; body mass index (BMI) = 19.31 ± 1.42 kgm-2) where skin tissue perfusion (TPsk) measurement was taken prior and posterior to massage/control sessions. Each of the three sessions incorporating different massage modes are marked by a significant difference in skin tissue perfusion (p<0.05) except for control session (p>0.05). Furthermore, post-hoc analysis demonstrates a significant increase in TPSk postsession deep tissue massage as compared to other two modes (blood circulation mode and sweet dreams mode). In the second part of the study, 6 males (age 23.33 ± 2.07 years; weight 68.42 ± 10.94 kg; height 180.30 ± 7.19 cm; body mass index (BMI) 20.92 ± 1.87) underwent MCT with only sweet dreams mode. Richards-Campbell Sleep Questionnaire (RCSQ) and wrist actigraphy were used to assess variations in sleep parameters pre- and post-session. While our evidence for effectiveness of massage in improving key sleep parameters is inconclusive, results regrading skin tissue perfusion indicate that there may potentially be positive impact of massage on circulation.